Yb3+ doped single-mode silica fibre laser system for high peak power applications - Franczyk, Marcin; Pysz, Dariusz; Włodarczyk, Filip; Kujawa, Ireneusz; Buczyński, Ryszard (Photonics Letters of Poland, 2020)
We present ytterbium doped silica single-mode fibre components for high power and high energy laser applications. We developed in-house the fibre laser with high efficiency of 65% according to the launched power, the threshold of 1.16W and the fibre length of 20 m. We also elaborated the fibre with 20 µm in diameter core suitable for amplifying the beam generated in oscillator. We implemented made in-house endcaps to prove the utility of the fibre towards high peak power applications. Full Text: PDF References Strategies Unlimited, The Worldwide Market for Lasers: Market Review and Forecast, 2020 DirectLink J. Zhu, P. Zhou, Y. Ma, X. Xu, and Z. Liu, "Power scaling analysis of tandem-pumped Yb-doped fiber lasers and amplifiers", Opt. Express 19, 18645 (2011) CrossRef IPG Photonics, Product information, accessed: October, 2020. DirectLink J.W. Dawson, M. J. Messerly, R. J. Beach, M. Y. Shverdin, E. A. Stappaerts, A. K. Sridharan, P. H. Pax, J. E. Heebner, C. W. Siders, and C. P. J. Barty, "Analysis of the scalability of diffraction-limited fiber lasers and amplifiers to high average power", Opt. Express 16, 13240 (2008) CrossRef W. Koechner, "Solid-State Laser Engineering", Springer Series in Optical Science, Berlin 1999 CrossRef A. V. Smith, and B. T. Do, "Bulk and surface laser damage of silica by picosecond and nanosecond pulses at 1064 nm", Appl. Opt. 47, 4812 (2008), CrossRef M. N. Zervas, C. Codemard, "High Power Fiber Lasers: A Review", IEEE J. Sel. Top. Quantum Electron. 20, 1, 2014 CrossRef D.J. Richardson, J. Nilsson, and W.A. Clarkson, "High power fiber lasers: current status and future perspectives [Invited]", J. Opt. Soc. Am. B, 27, 63, 2010, CrossRef M. Li, X. Chen, A. Liu, S. Gray, J. Wang, D. T. Walton; L. A. Zenteno, "Limit of Effective Area for Single-Mode Operation in Step-Index Large Mode Area Laser Fibers", J. Lightw. Technol., 27, 3010, 2009, CrossRef J. Limpert, S. Hofer, A. Liem, H. Zellmer, A. Tunnermann., S. Knoke, and H. Voelckel, "100-W average-power, high-energy nanosecond fiber amplifier", App.Phys.B 75, 477, 2002, CrossRef